Evaluating the Impact of Deceptive Marketing and Advertising on Customer Loyalty - Neama, Nagham Hussein; AL-Sammarraie, Marwah Mahmood (Journal of Ecohumanism, 2024)
Promotion of products in the digital sphere through electronic applications or social media platforms such as YouTube and Facebook, using misleading marketing and advertising strategies and methods; misleading consumers through multiple channels; and sensitizing customers to the nature of marketing and misleading advertising in Iraq's e-marketing sector. This research aims to do two things, except to identify misleading marketing practices in the area of (product/service, price, promotion/marketing), and to determine how these trick marketing practices affect customers loyalty applications that were part of the sample study. Finally, the Toters App has been set. The study sample consisted of 409 individuals contacted through the users of the site; data was collected using the questionnaire. The study has resulted in evidence that a statistically significant moral significance between deception in the product and the level of customer loyalty, a statistically significant moral significance between price deception and customer loyalty, a statistically significant moral significance between marketing deception and customer loyalty. The study reached recommendations, including efforts to raise consumer awareness of the concept of deceptive marketing, to provide examples of deceptive practices, and to enhance customer confidence in the honesty of offers and the truth of offers. There must be a clear and frank explanation of the increase in prices within exhibitions without changing the capacity and size of the product or quality, and working to renew the customer's confidence of the same promoter and in which he had previous negative experiences.